LIMD1 Increases the Sensitivity of Lung Adenocarcinoma Cells to Cisplatin via the GADD45α/p38 MAPK Signaling Pathway - Zeng, Xiaofei; Wang, Hong; He, Dongsheng; Jia, Weikun; Ma, Ruidong (Frontiers in Oncology, 2020)
Objective To investigate the effect of LIMD1 on the sensitivity of lung adenocarcinoma cells to cisplatin and explore the mechanism. Methods A549 and H1299 cells were transfected with lentivirus to establish LIMD1-overexpressing cell lines and their respective controls. The protein expression of GADD45α and p38 MAPK was detected by Western blot. The survival of A549-vec, A549-LIMD1, H1299-vec and H1299-LIMD1 cells after cisplatin treatment was observed by CCK-8, and the viability was calculated accordingly. Then, SB203580 was used to inhibit the activity of the p38 MAPK signaling pathway, after which the survival of A549-vec, A549-LIMD1, H1299-vec and H1299-LIMD1 cells in response to cisplatin was observed again by CCK-8, and the viability was calculated accordingly. Results When LIMD1 was overexpressed in A549 and H1299 cells, the levels of GADD45α and p-p38 MAPK were increased, but total p38 MAPK expression showed no significant change. After adding 30 µM cisplatin, the optical density (OD) values ​​of A549-LIMD1 and H1299-LIMD1 cells were significantly lower than those of their respective controls at 24 h, 48 h and 72 h; the viability of A549-LIMD1 and H1299-LIMD1 cells was significantly lower than that of their respective controls at all the times tested (p<0.05). The Western blot results showed that the expression of apoptotic proteins cleaved caspase 3 and cleaved PARP in cisplatin-treated A549-LIDM1 and H1299-LIMD1 cells was significantly higher than that in their respective control cells. Flow cytometry showed that the apoptosis rates of A549-LIMD1 and H1299-LIMD1 cells were significantly higher than those of their respective controls (p<0.05). SB203580 significantly inhibited the activation of the p38 MAPK signaling pathway in lung adenocarcinoma cells; however, neither the OD values nor the viability ​​of A549-LIMD1 cells and H1299-LIMD1 cells showed no significant difference from those of their controls at 24 h, 48 h and 72 h after cisplatin and SB203580 treatment (p>0.05 for both). Western blot analysis showed that after SB203580 was added, the expression of cleaved caspase 3 and cleaved PARP in A549-LIMD1 and H1299-LIMD1 cells presented no significant difference compared with that in their respective controls. Conclusion LIMD1 increases the sensitivity of lung adenocarcinoma cells to cisplat